Proceedings of the 2nd International Conference on Technology and Educational Science (ICTES 2020) 2021
DOI: 10.2991/assehr.k.210407.275
|View full text |Cite
|
Sign up to set email alerts
|

Development of Learning Videos Based Discovery Learning for Class V Elementary School Temperma Material

Abstract: This study aims to determine the feasibility of learning videos based on Discovery Learning of human respiratory system content in science class V SD No. 1 Mengwi. The research method used is 4D (Define, Design, Development, Disseminate). In collecting the research data, it is prioritized to use a questionnaire method and complete interviews and observations. The data analysis techniques used in this study are quantitative analysis and qualitative analysis. In this study the data were sourced from students, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Media pembelajaran merupakan alat atau sumber yang memudahkan penyebaran informasi, pengetahuan, dan keterampilan untuk menunjang proses pembelajaran (N. K. P. Dewi & Suniasih, 2021). Media pembelajaran berperan penting dalam melibatkan siswa, merangsang minat mereka, dan membantu pemahaman konsep (Sabil et al, 2021).…”
Section: Definisi Media Pembelajaran Paiunclassified
“…Media pembelajaran merupakan alat atau sumber yang memudahkan penyebaran informasi, pengetahuan, dan keterampilan untuk menunjang proses pembelajaran (N. K. P. Dewi & Suniasih, 2021). Media pembelajaran berperan penting dalam melibatkan siswa, merangsang minat mereka, dan membantu pemahaman konsep (Sabil et al, 2021).…”
Section: Definisi Media Pembelajaran Paiunclassified
“…The influence of the Think Pair Share model assisted by Quizizz learning media on results studying social studies process for students in a way active develop potency himself For own religious spiritual power, control self, personality, intelligence, morals noble, as well required skills himself, society, nation and state ( Kartiko et al, 2020) ." Education is business conscious and planned For direct or help develop potency physical and spiritual given to Students by adults For mature and achieve goal for Students can in a way independent fulfil task his life (Dewi et al, 2023) . Based on opinion above can concluded that education is something business conscious, planned and carried out in a way systematic in mature man through the learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Learning will be meaningful if students participate actively, both physically and mentally. As a result, teachers must be able to create an environment that engages students in the learning process (Dewi & Suniasih, 2020;Duran et al, 2015;Gever et al, 2021). Teachers can create a learning environment that activates students physically and mentally by using their own learning innovations.…”
Section: Introductionmentioning
confidence: 99%